STUDI KASUS MENGENAI TINGKAT KEAKTIFAN BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Septi Nurmila Sari; Deviyanti Pangestu; Roy Kembar Habibi; Erni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the level of learning activeness among students at SDN Baniaga, focusing on aspects of collaboration, engagement, and motivation. The research employed a case study approach involving questionnaires, observations, and interviews with 30 fifth-grade students. The findings reveal that students demonstrate relatively high levels of collaboration and engagement; however, challenges remain in terms of motivation and active participation. These results highlight the need for implementing more interactive and inclusive learning strategies to enhance student learning activeness. This study is expected to serve as a reference for educators and schools in creating a learning environment that supports both academic and social development of students.